Infective agents in diabetic foot ulcers and their sensitivity patterns - Mehmood Nadir , Muhammad Qasim Khan , Malik Irfan Ahmed , Muhammad Anwar Idrees ,Tehzeeb ul Hassan , Maha Nadir (Journal of Rawalpindi Medical College, 2021)
Background: Diabetic-foot syndrome is a difficult & debilitating complication of inadequately regulated Diabetes Mellitus. Attributed to neural & vascular pathology, the condition is further potentiated by glycemic healing impairment. A wide array of microorganisms have been implicated & sensitivity-guided antibiotics are essential to save both limb as well as to minimize rampant microbial resistance. Present study aims to determine the culture & sensitivity pattern of bacteria in stated cohort of patients at a Surgical Unit. Materials & Methods: This prospective cohort study was conducted over a period of 1 year-duration at a tertiary-care-Hospital. All patients presenting with diabetic-foot who had not been subjected to empiric antibiotic-therapy were enrolled. Demographic & lesion-based variables were studied and the Culture & Sensitivity pattern was evaluated and statistically analyzed. Results:100 patients were included in the study,of which 80 were male (mean-age 60.8±12.7 years) & rest female (mean-age 58.4±11.3-years).35% cultures yielded no growth. Remaining cases showed following pathogens in descending order of incidence. Maximal sensitivity was also reported as mentioned. 1) Staphylococcus-aureus & Klebseilla-Pneumoenae– Piperacillin/Tazobactam,2) Pseudomonas-Aerugionas-Cefotaxime,3)E-coli–Amikacin& Sulbactam,4) Proteus -Gentamicin, 5) Streptococci– Amikacin and 6) Bacteroides – Cefoperazone & Aztreonam. Of 71 cases, 70 had aerobic-organisms isolates & only 1 had anaerobic-isolate. Conclusions: Six pathogens were identified in present study of which Staphylococcus-Aureus was the most prevalent as well as the most resistant. Streptococci & Gram-negative Organisms were observed in remaining cases. While formulation of an adequate antibiotic regime is rendered difficult by resistance & mixed infections, targeted antibiotic administration is decisively crucial to achieve optimal & timely outcome in diabetic foot.